NAZOPHARYNGOENDOSCOPIC STUDY OF THE VELOPHARYNGEAL RING FUNCTION - O. Nelyubina; A. A. Mamedov (Union of pediatricians of Russia, 2012)
This paper presents the application of nazopharyngoendoscopic study to assess the function of the velopharyngeal ring in children having congenital cleft lip and palate, as well as the velopharyngeal insufficiency. The effectiveness of surgical treatment of the defect of hard and soft palate and velopharyngeal insufficiency depends on the maximum restoration degree of the velopharyngeal ring muscle structures correct orientation.